2020
DOI: 10.1111/cpf.12613
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between heart rate variability and carotid intima‐media thickness in the Brazilian Longitudinal Study of Adult Health – ELSA‐Brasil

Abstract: Background Both increased carotid intima-media thickness (cIMT) and low heart rate variability (HRV) have been associated with cardiovascular mortality and morbidity. Thus, the aim of this study was to investigate whether cardio autonomic alterations are accompanied or not by subclinical atherosclerosis in participants of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Methods cIMT measures and 5-min HRV analyses were performed in apparently healthy adults. Heart rate variability was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Endothelial dysfunction was also associated with decreased HRV in healthy adults and patients with stable coronary artery disease or diabetes mellitus [39][40][41]. Increased carotid intima-media thickness was associated with decreased HRV in previous studies [42,43]. Our previous studies showed that urinary phthalate metabolites were associated with endothelial dysfunction, insulin resistance, and increased carotid intima-media thickness [13,14,44].…”
Section: Discussionmentioning
confidence: 79%
“…Endothelial dysfunction was also associated with decreased HRV in healthy adults and patients with stable coronary artery disease or diabetes mellitus [39][40][41]. Increased carotid intima-media thickness was associated with decreased HRV in previous studies [42,43]. Our previous studies showed that urinary phthalate metabolites were associated with endothelial dysfunction, insulin resistance, and increased carotid intima-media thickness [13,14,44].…”
Section: Discussionmentioning
confidence: 79%
“…In a recent article, we detected lower HRV values in participants with high carotid intima-media thickness (cIMT), but independent relationships were not found in the overall sample ( 36 ). It is important to note that these different findings may be related to CAC and cIMT distinct performances in relation to subclinical atherosclerosis progression: cIMT reflects the first stages while CAC reflects later stages of the atherosclerotic process ( 37 ).…”
Section: Discussionmentioning
confidence: 91%
“…Cardiac autonomic impairment has also been associated with an increased risk of fatal and nonfatal CAD ( 6 , 7 ) and can be measured by heart rate variability (HRV) analysis. The clinical significance of this measure is increasingly recognized as an important physiological marker and a diagnostic tool in the detection of autonomic impairment and prediction/prognosis of several cardiac and non-cardiac disorders ( 8 - 13 ). Essentially, a combination of higher values of standard HRV indices under resting conditions means an adequate coupling between the sympathetic and the parasympathetic branches of the autonomic nervous system (ANS).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction was also associated with decreased HRV in healthy adults and patients with stable coronary artery disease or diabetes mellitus [39][40][41]. Increased carotid intima-media thickness was associated with decreased HRV in previous studies [42,43]. Our previous studies showed that urinary phthalate metabolites were associated with endothelial dysfunction, insulin resistance and increased carotid intima-media thickness [12,13,44].…”
Section: Discussionmentioning
confidence: 99%